KAEDAH PELAKSANAAN HUKUMAN SEBAT DI DALAM ISLAM - Md Hashim, Ashraf (Jurnal Syariah, 2019)
This article is an indepth research on the method oj the execution ojwhipping punishment under Islamic criminal law. The method applied under Islamic law is totally different than what has been practised under Malaysian law. The whipping punishment under Islamic law is not meant to severely injure a person physically, but it is meant to sufficiently deter him from committing a crime in the future and serve as an example and deterrent jar the public from committing such similar crimes.